A Systematic Study of Liquid Chromatography in Search of the Best Separation of Cannabinoids for Potency Testing of Hemp-Based Products - Ayowole Owolabi; Olalekan Ogunsola; Emma Joens; Medline Kotler; Liguo Song (Molecules)
A study was conducted to search for the best separation of eighteen cannabinoids, the maximum number of cannabinoids that have been quantified so far, for potency testing of hemp-based products using liquid chromatography diode array detector (LC-DAD). The investigation utilized four column types, all sharing the same dimension (150 mm × 2.1 mm) and core–shell particle size (2.7 µm), but different stationary phases: dimethyl-octadecyl (Poroshell 120 EC-C18), diisobutyl-octadecyl (Raptor ARC-18), reverse phase (RP)-carbamate (Cortecs Shield RP-18), and RP-amide (Ascentis Express RP-Amide). The resolution of adjacent cannabinoids was kept close to 1.5 or higher, while the separation time was kept as short as possible. The fastest separation was achieved within 15.0 min using two sequential Raptor ARC-18 columns, with a mobile phase consisting of 75.0% acetonitrile and 25.0% aqueous solution of 0.03% formic acid and 0.5 mM ammonium formate at pH 2.97, at a flow rate of 0.5 mL/min. A slightly improved resolution of the eighteen cannabinoids was obtained within 18.5 min using two sequential Poroshell 120 EC-C18 columns under similar conditions, except for a mobile phase containing 77.5% acetonitrile and a reduced flow rate of 0.45 mL/min due to backpressure higher than 600 bars. Furthermore, a rapid 7.0 min separation was achieved for potency testing of hemp-based products by liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI/MS/MS) using a Cortecs Shield RP-18 column, with a mobile phase consisting of 70.0% acetonitrile and 30.0% aqueous solution of 0.01% formic acid and 1 mM ammonium formate at pH 3.38 at a flow rate of 0.5 mL/min.